1963
DOI: 10.1111/j.1600-0447.1963.tb07471.x
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalographic Investigation of Alcoholics

Abstract: In 1953 Funkhouser, Nagler & Walke published an analysis of 334 electroencephalograms recorded from 189 alcoholics. Their main result was that electroencephalographic abnormalities were to be found in 21 $% of those cases in which there was no history of convulsions. Psychotic symptoms (delirium tremens or alcoholic hallucinations) did not increase the frequency of abnormality. Where there had, on the other hand, been convulsions, the number of abnormal electroencephalograms rose to the double.Delay, Verdaux &… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

1972
1972
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 7 publications
1
16
0
Order By: Relevance
“…For instance, early studies have found an association between having LV EEG and alcohol dependence in primarily EuroAmerican populations (Arentsen and Sindrup, 1963; Coger et al, 1978; Jones and Holmes, 1976; Varga and Nagy, 1960), and more recently this was verified in a Hispanic population (Ehlers and Phillips, 2007). In another study a subgroup of alcoholics with anxiety disorders were found to be more likely to have a low voltage alpha EEG, as compared to non-alcoholics (Enoch et al, 1995, 1999).…”
Section: 0 Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…For instance, early studies have found an association between having LV EEG and alcohol dependence in primarily EuroAmerican populations (Arentsen and Sindrup, 1963; Coger et al, 1978; Jones and Holmes, 1976; Varga and Nagy, 1960), and more recently this was verified in a Hispanic population (Ehlers and Phillips, 2007). In another study a subgroup of alcoholics with anxiety disorders were found to be more likely to have a low voltage alpha EEG, as compared to non-alcoholics (Enoch et al, 1995, 1999).…”
Section: 0 Discussionmentioning
confidence: 97%
“…For instance, in early studies, a cross-sectional association between having a relatively lower voltage EEG and alcohol dependence was found in primarily EuroAmerican populations (Arentsen and Sindrup, 1963; Coger et al, 1978; Jones and Holmes, 1976; Varga and Nagy, 1960). More recently it has been demonstrated that LVEEG records may be four times more common in some types of alcoholics, particularly those with anxiety, as compared to non-alcoholics (Enoch et al, 1995, 1999).…”
Section: 1 Introductionmentioning
confidence: 99%
“…Alterations in brain electrical activity have been described in both alcoholics and ASPD patients (Arentsen and Sindrup, 1963; Coger et al, 1978; Ehlers and Phillips, 2007; Enoch et al, 1999; Jones and Holmes, 1976, Lindberg et al, 2005). In this report, HTR3B was found to be associated with low alpha power in the resting EEG, an intermediate phenotype for AUD and ASPD (Lindberg et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Alpha power is a stable trait through healthy adulthood and is highly heritable (0.80) (Van Baal et al, 1996; van Beijsterveldt et al, 1996). Alcoholics appear to have reduced alpha power (Arentsen & Sindrup, 1963; Coger et al, 1978; Ehlers & Phillips, 2007; Enoch et al, 1999; Jones & Holmes, 1976). In a group of Finnish criminal alcoholics recruited from the same source population as one of the three samples within this study, an overall reduction in alpha power was observed in the waking EEG of participants with ASPD compared with age and gender-matched healthy controls (Lindberg et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In this connection it can be mentioned that a high incidence of EEG abnormalities has been found for psychopaths -particularly aggressive and in material mainly made up of men (e.g. 1,5,6,8,28). These abnormalities are normally in the form of bilateral nonspecific theta activity (nearly always involving the temporal lobes) but can be focal (particularly localized in the posterior temporal region).…”
Section: Discussionmentioning
confidence: 99%